2021
DOI: 10.17718/tojde.961836
|View full text |Cite
|
Sign up to set email alerts
|

Developing Measures for the Effectiveness of Distance Education as Regards Sustainability: The Mixed Method Approach

Abstract: Distance education has been acknowledged as a mechanism through which sustainable development can be achieved. The objective of the study is to develop the instrument that measures the effectiveness of distance education in inculcating sustainability among distance learners as the researchers have observed the absence of comprehensive and contextually appropriate measures for the effectiveness of distance education in nurturing sustainability. A mixed method research design was employed by following the six-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…This framework encompasses elements such as infrastructure, organizational structure, curriculum and content, professional development, and the integration of e-learning into higher learning institutions. Additionally, this study incorporated attributes identified by Azeiteiro, et al [8], which were subsequently empirically examined by Harizan and Hilmi [10]. These attributes encompassed aspects such as the quality of instructors, collaborativ e work, learning materials and activities, and the use of pedagogical skills.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This framework encompasses elements such as infrastructure, organizational structure, curriculum and content, professional development, and the integration of e-learning into higher learning institutions. Additionally, this study incorporated attributes identified by Azeiteiro, et al [8], which were subsequently empirically examined by Harizan and Hilmi [10]. These attributes encompassed aspects such as the quality of instructors, collaborativ e work, learning materials and activities, and the use of pedagogical skills.…”
Section: Methodsmentioning
confidence: 99%
“…The notion of sustainability is widely seen as crucial in addressing multifaceted environmental and societal challenges and is considered essential for the well-being of both current and future generations [7]. Despite these notions, there remains a limited body of research exploring how sustainability can be quantified within online and distance education programmes [8][9][10]. Consequently, evaluating the sustainability of these programmes remains a complex endeavor [10].…”
Section: Background Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement instruments were adapted from previous studies. Attitude towards sustainability was adapted from Gale et al (2014) and Yatim et al (2012), effectiveness of distance education was adapted from Harizan and Hilmi (2021), barriers to sustainability in distance education was adapted from Aleixo et al (2016) and innovativeness was adapted from Herrero Crespo and Rodríguez del Bosque (2008). All items, except for the socio-demographic characteristics, were measured using a four-point Likert scale (1 = Strongly disagree to 4 = Strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…2009); Hindistan,Vyas-Doorgapersad (2011); Nijerya,Oladipo (2016); Salgın döneminde 45 ülke deneyimi,Sangster, Stoner ve Flood (2020); Malezya,Harizan ve Hilmi (2021); Rusya,Rybakova, vd. (2021), ülkemizde de muhasebe eğitiminde hem lisans ve lisansüstü düzeyde hem de mesleki gelişim için yaşamboyu öğrenme süreçlerinde açık ve uzaktan öğretim kaynaklarından geniş ölçüde yararlanılmaktadır.…”
unclassified